Relating Physiologic Swallowing Impairment, Functional Swallowing Ability, and Swallow-Specific Quality of Life - Hazelwood, R. Jordan; Armeson, Kent E.; Hill, Elizabeth G.; Bonilha, Heather Shaw; Martin-Harris, Bonnie (Dysphagia, 2023)
Many studies include functional swallowing ability and quality of life information to indicate a response to a specific swallowing intervention or to describe the natural history of dysphagia across diseases and conditions. Study results are difficult to interpret because the association between these factors and actual swallowing impairment is not understood. We set out to test the associations between components of physiologic swallowing impairment, functional swallowing ability, and swallow-specific quality of life using standardized and validated measurement tools: Modified Barium Swallow Impairment Profile (MBSImP), Functional Oral Intake Scale (FOIS), Eating Assessment Tool (EAT-10), and Dysphagia Handicap Index (DHI). We specifically aimed to understand which factors may contribute to the overall relationships between these measurement tools when analyzed using total scores and item-level scores. This study included a heterogeneous cohort of 273 outpatients who underwent a modified barium swallow study (MBSS). We found significant correlations between MBSImP total scores and FOIS scores and DHI total scores, but not between MBSImP total scores and EAT-10 total scores. Significant correlations were also found between MBSImP item-level component scores and FOIS scores, EAT-10 total scores, and DHI total scores. Detailed item-level analyses revealed the MBSImP components of bolus transport/lingual motion, oral residue, and tongue base retraction were correlated with EAT-10 item-level scores and DHI item-level scores. The clinically modest associations between physiologic swallowing impairment, functional swallowing ability, and swallow-specific quality of life reveal different factors that uniquely contribute to patients’ overall dysphagic profile, emphasizing the clinical impact of a comprehensive swallowing assessment.